Teaching in the New Normal through the Lenses of English Teachers - Nedamo, Natashia-Ann B.; Pineda, Jesusa E. (International Journal of Humanities and Education Development (IJHED), 2023)
This study looked into the challenges that two Senior High School teachers of English and four Junior High School teachers who taught in a Schools Division in one of the cities in the Philippines encountered in teaching English to high school students, into their coping strategies, and into the insights they gained into such experiences vis-à-vis lesson preparation, lesson delivery, modular teaching modality, and assessment of students’ outputs in the New Normal during the School Year 2020-2021. Narrative research design was employed, and thematic analysis was used to identify, analyze, and interpret patterns of meaning within the data provided by the participants who composed the entire population. The findings reveal the following themes that were gleaned from the participants’ responses. As for the challenges the participants encountered, the following themes were obtained: (1) Preparing Learning Activities that Best Suit Students’ Needs; (2) Finding Ways and Means to Reach Out to Students; (3) Lack of Supervision Engenders Unanswered Retrieved Modules or Unreturned Modules; and (4) Ensuring the Authenticity of Students’ Answers. As regards the coping strategies the participants employed in dealing with the challenges they encountered, the following themes were derived: 1) Functioning at an Optimal Level by Engaging in Favorable Plans of Action; (2) Strategizing Ways to Promote Transfer of Learning; (3) Exuding Optimism and Providing Avenues to Facilitate Distance Learning; and (4) Making Room for Students to Submit Well-thought-out Outputs. With respect to the insight gained by the participants into the challenges they came up against and into the coping strategies they utilized to face up to those challenges, the following themes were attained: (1) Flexible and Enthusiastic Teaching Lead to Successful Lesson Planning; (2); Communication, Creativity, and Corroboration Foster Comprehension Amongst Students (3) Communication and Patience Cultivate an Environment Conducive to Modular Distance Learning; and (4) Devising a Course of Action for Evaluating Students’ Work is Propitious. Indeed, the teachers had the fortitude to face the difficulties that the New Normal brought and discovered that communication, creativity, corroboration, patience, and a plan for evaluating students' outputs could all contribute to effective teaching and learning.